Immigrant assimilation and profiles of breast cancer screening behaviors among U.S. immigrant women. Issue 2 (19th April 2021) - Ghirimoldi, Federico; Sanchez-Soto, Gabriela
Abstract: Previous researchers have shown that despite increased prevention and cancer risk awareness, many immigrant women do not receive cancer screenings in a timely manner. We use data from the National Health Interview Survey and Latent Class Analysis to characterize immigrant women in the U.S. in accordance to their risk of engaging in breast cancer prevention. We identify three latent profiles based on use of cancer screenings, sociodemographic characteristics, family cancer history, and immigrant acculturation. Our results show that cancer screening behaviors of immigrants are consistent with patterns of both classic and segmented assimilation, as well as with greater immigrant diversity.